Brasil, balanço econômico, sucessos e limites - Salama, Pierre (Estudos Avançados, 2010)
It appears that successive governments under Lula's presidency followed two opposite economic philosophies. The first one, the monetarist philosophy, aims to curb increases in prices: very high real interest rates, important primary budget surpluses, appreciation of the national currency. This explains the difficulties in raising investment rates, in raising the added value of products and in promoting the development of production of high technology content products. The secon one, Keynesian, aims to reduce inequalities, to raise minimum real wages and to ensure wider social security cover. It explains high growth rates and domestic market renewed dynamics. Because of the international crisis, this second philosophy influences economic policies more heavily than in the past, and offers an opportunity to enter a new era, providing however that the obstacle of a regressive tax system is removed and providing the implementation for the future of a new, more active, industrial policy lowering the risks of primarisation currently threatening Brazil.